120k views
18 votes
(2x)⁴ = (2x)(2x)(2x)(2x)
(xy)⁷ =
(-ab)⁶ =

write in expanded form​

2 Answers

10 votes

Hello!

Answer:


\Large \boxed{ \sf (xy)(xy)(xy)(xy)(xy)(xy)(xy)\\\\ }\\\Large \boxed{ \sf (-ab)(-ab)(-ab)(-ab)(-ab)(-ab)\\\\ }\\

Explanation:

The base of an exponent represents the number that is multiplied by itself.

The exponent of a base indicates the number of times the base is multiplied by itself.

So:


\sf (2x)^4 = (2x)(2x)(2x)(2x)\\\\(xy)^7 =(xy)(xy)(xy)(xy)(xy)(xy)(xy)\\\\(-ab)^6 = (-ab)(-ab)(-ab)(-ab)(-ab)(-ab)

User TeFa
by
5.8k points
3 votes

Explanation:

(xy)(xy)(xy)(xy)(xy)(xy)(xy)

(-ab)(-ab)(-ab)(-ab)(-ab)(-ab)

User Mike Vosseller
by
4.7k points